Effects of exercise on secretion transport, inflammation, and quality of life in patients with noncystic fibrosis bronchiectasis Protocol for a randomized controlled trial - Santos, Daniele Oliveira dos; Dutra de Souza, Hugo Celso; Baddini-Martinez, Jose Antonio; Cipulo Ramos, Ercy Mara [UNESP]; Gastaldi, Ada Clarice (Lippincott Williams & Wilkins, 2018)
Background: Bronchiectasis is characterized by pathological and irreversible bronchial dilatation caused by the inefficient mucus and microorganism clearance and progression of inflammatory processes. The most frequent characteristic is the increase in bronchial mucus production resulting in slower transport and damage to the mucociliary transport. Aims: To evaluate the effects of exercise on mucus transport, inflammation, and resistance of the respiratory and autonomic nervous systems and subsequent effects on quality of life in patients with bronchiectasis who are enrolled in a pulmonary rehabilitation program. Methods: Sixty subjects of both sexes between 18 and 60 years (30 volunteers with clinically stable bronchiectasis and 30 healthy volunteers) will be included. Participants with chronic obstructive pulmonary disease, decompensated cardiovascular or metabolic diseases, neuromuscular and musculoskeletal diseases, and active smokers will be excluded. Volunteers will be randomly allocated to the pulmonary rehabilitation or control groups. The primary outcomes will be nasal transport time as evaluated by nasal saccharin transport time, analysis of nasal lavage, enzyme immunoassay of exhaled expiration, and analysis of the mucus properties. The secondary outcomes will include pulmonary function tests, impulse oscillometry, heart rate variability analysis, and quality of life questionnaires. Discussion: In addition to the benefits for patients already described in the literature, the additional benefit of mucus removal may contribute to optimizing treatments and better control of the disease. Conclusion: This protocol could provide new information about the unclear mechanisms regarding exercise to aid in the removal of secretions.
Keywords: bronchiectasis; clinical trial; exercises; inflammation; mucociliary clearance; rehabilitation